Legal Analysis of Brimob's Repressive Actions in Handling Demonstrations Between Law and Human Rights from the Perspective of Law Number 39 of 1999 Concerning Human Rights - Kaharuddin Siregar; Risdalina Risdalina; Muhammad Khoirul Ritonga (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
This article discusses a legal analysis of repressive actions by the Mobile Brigade Corps (Brimob) in handling demonstrations in Indonesia. The main focus is directed at the compliance of the authorities' actions with the principles of law enforcement and human rights protection as stipulated in Law Number 39 of 1999 concerning Human Rights. The use of force in demonstrations often raises controversy regarding the limits of authority, the legality of the actions, and the impact on citizens' basic rights such as the right to assemble, express opinions, and obtain protection from arbitrary action. This research uses a normative approach by reviewing laws and regulations, legal literature, and international human rights standards. The analysis results show that Brimob's repressive actions must always be based on legality, necessity, proportionality, and accountability to ensure human rights protection. However, in practice, violations that contradict human rights principles, especially related to the use of excessive force, are still found. This article emphasizes the importance of strengthening regulations, human rights training for officers, and more effective oversight mechanisms.